Development of the Processing Procedure for Palm Fiber with Communities for Industrial Handmade Product Creation - Songwut Egwutvongsa; Somchai Setvisat; Thanat Pirumgran (My University, 2021)
This research used a mixed-methods approach to focus on the properties and satisfaction assessment of effectiveness for palm fibers in the Khonsan Sub-District community group in Chaiyaphum province with a total of 113 people. In addition, the study used a 5-point rating scale which had a Cronbach’s Alpha Coefficient value at the level of 0.97, in addition to two-way ANOVA. The study presented testing results by ordering from coconuts, palms, betel nuts, and tans with the fiber tensile ratings of 67.45 N, 57.19 N, 56.75 N, 52.49 N, and fiber tensile ratings of 6.80%, 7.30%, 7.12%, and 6.25%, respectively. In this case, the betel nut fibers and tan fibers showed durability to wet washing and the dry period as the most common way. Thus, the satisfaction assessment of tan fibers was at the most satisfactory level, (Mean=4.49, S.D. =0.57), followed by the coconut fibers at the excellent level, (Mean = 4.47, S.D. =0.56) and the betel nut fibers at the moderate level, (Mean=3.35, S.D. =0.71). Levene’s test showed that p was equal to 0.00, indicating that the factors of type and properties of palm fibers were at a varied level with statistical significance. Similarly, the fiber characteristics and properties of palm fibers for each type had an F value equal to 11.45 and Sig. equal to 0.00. In addition, it was found that there was at least one pair different from other pairs, such as coconut fibers and tan fibers. Consequently, the research with community participation showed that it appeared to confirm the balance between the effectiveness of materials, labor skills, human labor, and the stabilization of life. As a result, it affected the satisfaction at the excellent level for people in the development communities (Mean=4.10, S.D. =0.78).

Received: 12 January 2021 / Accepted: 24 March 2021 / Published: 10 May 2021
Keywords: Agricultural and Environmental Management